Problematika Tataran Sistem pada Pekerja Sosial Masyarakat (PSM) sebagai Relawan Sosial di Kota Payakumbuh - Fatasa, Uzika Putri; Erwin, Erwin; Meiyenti, Sri (FISIP Universitas Malikussaleh, 2024)
Community social workers (PSM) are government partners in implementing social welfare programs with the status of social volunteers. However, in its implementation, the burden of the main tasks and functions of PSM is quite diverse and varies according to the number of programs carried out by the government. This study aims to find out the problems that arise in Community Social Workers in carrying out their roles without an honorarium given by the Ministry of Social Affairs Regulation Number 10 of 2019. The research was conducted in the Kapalo Koto Dibalai Village and the Parit Rantang Village which had an extreme impression of the Beneficiary Families (KPM) against PSM. This study uses qualitative research methods and a case study approach, and collects data by means of observation and interviews. The results of this study there are various problems that arise, among others; the potential for extortion, domestic affairs affecting performance, side jobs affecting performance optimization, enduring status as a source of societal stigma against PSM.